Regioselective C3-Formylation of 2H-Indazoles Using Selectfluor under Microwave-Assisted Conditions - Pitchai, Manivel; Kaspady, Mahammed; Indasi, Gopikumar; Krishnan, Rajesh; Maheswarappa, Gururaju Sannakki; Vetrichelvan, Muthalagu; Mathur, Arvind; Gupta, Anuradha (SynOpen, 2024)
An efficient microwave-assisted Selectfluor-mediated regioselective C3-formylation of 2H-indazoles bearing a variety of alkyl and aryl substituents using DMSO as the formylating agent has been developed. This methodology provides access to 3-formyl 2H-indazoles with moderate to excellent yields. These functionalized indazoles are potentially useful as templates for drug discovery. Control experimental results suggest that this formylation probably proceeds through a radical pathway.
Keywords: 2H-indazoles; Selectfluor; C3-formylation; microwave; radical pathways